Pendampingan Digital Marketing pada Usaha Pengelolaan Limbah Fashion di BUMDesa Berkaho Desa Pungpungan Kecamatan Kalitidu: Pengabdian - Muhammad Rizqi Agustino; Dwi Irnawati; Kustaji; Reza Anggapratama; Fauzian Noor; Vicky Eka Prasetya (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The issue of textile waste and second-hand clothing has become a global concern, also affecting Indonesia, including its rural areas. Pungpungan Village, through its Village-Owned Enterprise (BUMDesAberkaho), has taken an innovative step by transforming fashion waste into economically valuable handicrafts such as bags and doormats. Although this initiative creates opportunities for community empowerment—particularly for housewives and youth—significant challenges remain in the area of marketing. Limited branding strategies and low digital literacy have prevented these upcycled products from gaining wider recognition, with sales still confined to local markets. This community engagement program aims to provide digital marketing assistance to entrepreneurs under BUMDesAberkaho. The focus of the activities includes training on storytelling-based branding, the creation of engaging visual content, the optimization of social media and online marketplaces, and the development of digital collaboration strategies with local communities and influencers. A participatory and educational approach is applied to ensure that participants can directly implement the knowledge in their businesses. Through this mentoring, it is expected that the upcycled handicraft products from Pungpungan Village can compete in broader digital markets and support a village-based circular economy